2022
DOI: 10.1155/2022/4933015
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Catechins from Aegle marmelos Fruit Pulp: Statistical Optimization Using Response Surface Methodology and Artificial Neural Networks

Abstract: Aegle marmelos is a medicinal herb that has a variety of biological constituents. “Catechins” are a class of phenolic compounds that have therapeutic value. The present study employs batch extraction with methanol as a solvent to extract the catechins from the pulp of Aegle marmelos fruit. Box–Behnken design of response surface methodology (RSM-BBD) is used to optimize the operational parameters impacting catechin extraction, such as solvent concentration, pH, and extraction time. Extraction of 96.5% of catech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Vuong et al (2013) [31] reported that individual catechins usually maintain their stability at a pH of 4 or slightly lower, with extraction efficiency decreasing at higher pH levels, probably due to their degradation, which is known to occur at a pH of 5 and above [32]. Additionally, Kurimilla et al (2022) [33] reported that, although catechins are usually stable at acidic pH levels up to 4, extremely low pH conditions can enhance their degradation when employing high extraction temperatures. This aligns with the result obtained here, where higher amounts of catechin for treatment times exceeding 5 min were notably obtained for pH 4.…”
Section: Flavonoids Flavanols and Tanninsmentioning
confidence: 99%
“…Vuong et al (2013) [31] reported that individual catechins usually maintain their stability at a pH of 4 or slightly lower, with extraction efficiency decreasing at higher pH levels, probably due to their degradation, which is known to occur at a pH of 5 and above [32]. Additionally, Kurimilla et al (2022) [33] reported that, although catechins are usually stable at acidic pH levels up to 4, extremely low pH conditions can enhance their degradation when employing high extraction temperatures. This aligns with the result obtained here, where higher amounts of catechin for treatment times exceeding 5 min were notably obtained for pH 4.…”
Section: Flavonoids Flavanols and Tanninsmentioning
confidence: 99%
“…Te thermodynamic parameters measured are presented in Table 6. Te negative values of ΔG at various temperatures suggest that the adsorption process was spontaneous and thermodynamically feasible [31][32][33]. Te ΔG values slightly decrease with the increasing temperature, implying that more dye was adsorbed onto the adsorbent surface at higher temperatures.…”
Section: Adsorption Isothermsmentioning
confidence: 99%